Expression levels of GSTA2 and APOD genes might be associated with carotenoid coloration in golden pheasant (Chrysolophus pictus) plumage - GAO, Guang-Qi (Dongwuxue Yanjiu, 2016)
Carotenoids, which generate yellow, orange, and red colors, are crucial pigments in avian plumage. Investigations into genes associated with carotenoid-based coloration in avian species are important; however, such research is difficult because carotenoids cannot be synthetized in vertebrates as they are only derived from dietary sources. Here, the golden pheasant(Chrysolophus pictus)was used as a model in analysis of candidate gene expression profiles implicated in carotenoid binding and deposition. Using mass and Raman spectrometry to confirm the presence of carotenoids in golden pheasant feathers, we found C(40)H(54)O and C(40)H(56)O(2) in feathers with yellow to red colors, and in the rachis of iridescent feathers. The global gene expression profiles in golden pheasant skins were analyzed by RNA-seq and all six carotenoid binding candidate genes sequenced were studied by real-time PCR. StAR4, GSTA2, Scarb1, and APOD in feather follicles showed different expressions in red breast and orange nape feathers compared with that of iridescent mantle feathers. Further comparison of golden pheasant yellow rump and Lady Amherst's pheasant(Chrysolophus amherstiae)white napefeathers suggested that GSTA2 and APOD played a potential role in carotenoid-based coloration in golden pheasant.